CLINICAL AND SURGICAL APPROACH TO EPILEPSY REFRACTORY - Pedro do Valle Varela, João; Nasser Pauferro, Leonardo; Silva Santa Clara, Nicolly; Vitor Amorim Barbosa, João; Castello Agrizzi, Lucas; Giselle Batt, Jennifer; Silva de Carvalho, José; Lobato Ferreira, Juliana; Fairana Godeline Essali, Genese; Luiz Teixeira Fully, Fabio (Health and Society, 2024)
Refractory epilepsy is characterized by the persistence of epileptic seizures even after adequate use of at least two antiepileptic drugs. This condition represents a significant challenge in the treatment of epilepsy, requiring a more assertive clinical and, in some cases, surgical approach. This study aims to review and explore the clinical and surgical approach to refractory epilepsy, highlighting the available treatment options, indications, benefits and challenges faced by patients and health professionals. This is a bibliographic review, using qualitative premises, with the PubMed, Scopus, Web of Science and Scielo databases. To better refine the research, the health descriptors “epilepsy”, “surgical treatment”, “neurostimulation” and “refractory epilepsy” were used. The clinical approach to refractory epilepsy involves careful assessment of the patient, including a detailed clinical history, complete physical examination and complementary tests such as electroencephalogram (EEG), magnetic resonance imaging (MRI) and computed tomography (CT) of the brain. The aim is to identify the origin of the epileptic seizures and determine the best therapeutic strategy. Clinical treatment usually involves optimizing drug therapy, with adjustments to the doses of existing drugs or the introduction of new drugs. However, in many cases, the response to drug treatment is unsatisfactory, leading to consideration of surgical options. Surgery for refractory epilepsy can include removing the brain tissue responsible for epileptic seizures (temporal lobectomy, focal resection, etc.), deep brain stimulation or other less invasive techniques. These procedures aim to reduce the frequency and severity of epileptic seizures, improving the patient’s quality of life. The approach to refractory epilepsy requires a multidisciplinary and individualized assessment, taking into account the clinical characteristics and specific needs of each patient. Although clinical treatment is the first line of approach, surgery can be a viable option for those who do not respond adequately to antiepileptic drugs. It is essential that patients with refractory epilepsy are referred to specialized centers for a complete and appropriate evaluation of their case.